External financial dependence and firms' crisis performance across Europe - Peter S. Eppinger; Katja Neugebauer (University of Tübingen, Faculty of Economics and Social Sciences, 2021)
How do financial market conditions affect real economic performance? Empirical investigations of this question have often relied on measures of external financial dependence (EFD) that are constructed using U.S. data and applied to other countries under the assumption of a stable industry ranking across countries. This paper exploits unique, comparable survey data from seven European countries to show that correlations of EFD across countries are weak, casting some doubt on this assumption. We then use the novel survey-based EFD index to show that the global financial crisis had a disproportionately negative impact on the real performance of financially dependent firms. Further investigations highlight the importance of supply chains in propagating the credit shock.
urn:nbn:de:bsz:21-dspace-1113967; hdl:10900/111396
Keywords: G10; G30; L25; F14; G01; D22; 330; External financial dependence; financial constraints; financial crisis; firm performance